Analysis of Steel Hardness on Crowbars in the Hardening Process with Variations of Cooling Media - Anhar Khalid; Muhammad Kasim (International Journal of Educational and Life Sciences, 2025)
The steel hardening process through hardening aims to improve the hardness of steel by rapid heating and cooling. The refrigerant media used, such as brine, plain water, and oil, have a significant influence on the hardness of steel. This study aims to analyze the effect of refrigerant media variations on steel hardness after the hardening process. The research method used is a laboratory experiment, in which the steel specimen is heated to an austenitization temperature and cooled with three different cooling media. The hardness of the steel was tested using the Rockwell hardness test, and the microstructure results were analyzed with a metallographic microscope. The gap of this study is the lack of studies related to the influence of refrigerant media variations on steel hardness with a focus on application to crowbars. The results showed that the brine medium provided the highest hardness (98.7 kgf/mm²), followed by ordinary water (98.1 kgf/mm²) and oil (96.2 kgf/mm²). These results suggest that faster refrigerant media, such as brine, produce higher hardness. This study provides insight into the selection of the optimal refrigerant media to increase steel hardness, especially in industrial applications that require hard and durable steel.